Investigating the Validity of Achievement Tests in the Algerian Secondary Schools: The Case of EFL Classes in the Biskra Region - Ahmed Chaouki, Hoadjli (Sciences humaines, 2014)
يدور مضمون هذا المقال حول موضوع التقويم التربوي بصفة عامة و إشكالية بناء الاختبارات الفصلية بصفة خاصة بالمدرسة الجزائرية و تحديدا بالنسبة لطلبة الثانوي بولاية بسكرة ، تطرقنا لهذا الموضوع بالذات نابع من ملاحظاتنا الدائمة حول عدم وجود تطابق بين محتوى الاختبارات المقدمة لتلاميذ هذا الطور و ما يدرس خلال الفصل أو السنة الدراسية .و عليه فإن الهدف الأساسي لهذا المقال هو إجراء عملية تقويم لهذا النوع من الاختبارات و الوقوف على طريقة بنائها و ذلك من أجل تحديد النقائص و اقتراح بعض الإصلاحات لجعل هذه الاختبارات ذات فائدة.     This article sets out to explore the issue of evaluation in general and testing in particular within the Algerian context. The motives of such an investigation stems from the students' low scores that do not actually reflect their real performance by virtue of the non-pertinence between what students learn and what they are tested in. Therefore, the main purpose of the present article is to provide a comprehensive evaluation of the achievement tests to the EFL classes in the Biskra region.